2019
DOI: 10.1038/s41422-019-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

UFMylation of RPL26 links translocation-associated quality control to endoplasmic reticulum protein homeostasis

Abstract: Protein biogenesis at the endoplasmic reticulum (ER) in eukaryotic cells is monitored by a protein quality control system named ERassociated protein degradation (ERAD). While there has been substantial progress in understanding how ERAD eliminates defective polypeptides generated from erroneous folding, how cells remove nascent chains stalled in the translocon during co-translational protein insertion into the ER is unclear. Here we show that ribosome stalling during protein translocation induces the attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
232
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(241 citation statements)
references
References 62 publications
9
232
0
Order By: Relevance
“…In a recent paper published in Cell Research, Wang et al 8 reported that RPL26 ufmylation increases upon stalling of ER translocon-associated ribosomes. During synthesis of most membrane and secreted proteins, nascent peptides are cotranslationally translocated from translocon-docked ribosomes into the ER lumen, where they are folded, post-translationally modified, and trafficked elsewhere.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper published in Cell Research, Wang et al 8 reported that RPL26 ufmylation increases upon stalling of ER translocon-associated ribosomes. During synthesis of most membrane and secreted proteins, nascent peptides are cotranslationally translocated from translocon-docked ribosomes into the ER lumen, where they are folded, post-translationally modified, and trafficked elsewhere.…”
mentioning
confidence: 99%
“…Interestingly, Wang et al show that degradation of their reporter is inhibited but still occurs gradually when RPL26 ufmylation is completely ablated, suggesting that some ufmylationindependent RQC is also active at the ER. 8 The division of labor between distinct RQC pathways at the ER, and the types of stalling that ribosomal ufmylation can resolve, remain to be explored. Future work may also identify additional factors necessary for processing ufmylated ER-associated ribosomes.…”
mentioning
confidence: 99%
“…Our data set provides comprehensive evidence that different components of the translational machinery are UFMylated. We identified 27 ribosomal proteins as candidate substrates of the UFM1 system including RPS3 and RPL26, which recently have been characterized as UFM1 substrates (Simsek et al, 2017;Walczak et al, 2019;Wang et al, 2020). Mining peptides from a published deep proteome data set (Bekker-Jensen et al, 2017) for UFM1 modifications revealed that UFM1 remnant (valine-glycine, VG)-containing peptides were significantly enriched (p=0.00020929, Fisher's exact test) in candidates that passed our threshold ( Figure S4B and Table S2).…”
Section: The Translation Initiation Machinery Is Ufmylatedmentioning
confidence: 99%
“…However, thus far only reports by the Kopito, Cong and Ye laboratories provide a molecular explanation for a function of UFMylation in ER homeostasis: UFMylation and deUFMylation of the ribosomal subunit RPL26 contributes to co-translational protein insertion into the ER (Walczak et al, 2019) and promotes cotranslational quality control and degradation of stalled nascent polypeptides on ER-associated ribosomes (Wang et al, 2020). Further, UFMylation of DDRGK1 regulates the stability of the ER stress sensor IRE1a (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…7 C53 forms a tripartite receptor complex with the ufmylation E3 ligase UFL1 and its membrane adaptor DDRGK1 177 178 How is C53 recruited to the ER during ribosome stalling? Notably, C53 has been previously linked to 179 UFL1, an E3 ligase that mediates ufmylation of stalled, ER-bound ribosomes, modifying ribosomal protein 180 RPL26 Wang et al, 2019). To test if C53 forms a higher order receptor complex, we 181 analysed the interaction of C53 with UFL1 and its ER membrane adaptor DDRGK1 (Gerakis et al, 2019).…”
mentioning
confidence: 99%